Vanillic Acid Reduces Pain-Related Behavior in Knee Osteoarthritis Rats Through the Inhibition of NLRP3 Inflammasome-Related Synovitis - Ma, Zhenyuan; Huang, Zhengquan; Zhang, Li; Li, Xiaochen; Xu, Bo; Xiao, Yancheng; Shi, Xiaoqing; Zhang, Haosheng; Liao, Taiyang; Wang, Peimin (Frontiers in Pharmacology, 2021)
Objectives Synovitis plays an important role in knee osteoarthritis (KOA) pain. The activation of the nod-like receptor protein 3 (NLRP3) inflammasome in fibroblast-like synoviocytes (FLSs) promotes KOA development. In this study, we aimed to investigate whether vanillic acid (VA), a monomer derived from Chinese herbal medicines, could target NLRP3 inflammasome-related synovitis to reduce pain. Methods Rats in the KOA and KOA+VA groups were injected with monosodium iodoacetate (MIA) in the knee to induce KOA. From day 14, the KOA+VA group was given VA at 30 mg/kg every day via gastric intubation. FLSs were collected from the synovial tissues. We examined both the protein and gene expression of the caspase-1, apoptosis-associated speck-like protein with a caspase recruitment domain (ASC), NLRP3, components of the NLRP3 inflammasome, and interleukin-1β (IL-1β) and IL-18 in vivo and in vitro. Results The up-regulation of caspase-1, ASC, and NLRP3 in the KOA model were reduced by VA. VA also lowered the level of IL-1β and IL-18 in the KOA model. In addition, VA relieved pain-related behavior of KOA model rats and down-regulated the pain mediators CGRP, NGF, and TrkA in FLSs. Interestingly, we also observed a reduced synovial fibrosis in the animal experiments. Conclusion Our research showed that VA reduces synovitis and pain related behaviours in a rat model of KOA, which provides the basis for further investigations into the potential therapeutic impact of VA in KOA.